Purification effect and microorganisms diversity in an Acorus calamus constructed wetland on petroleum-containing wastewater. Issue 1 (1st January 2020) - Xiang, Wei; Xiao, Xin; Xue, Junyin
ABSTRACT: A constructed wetland system with Acorus calamus ( A. calamu s) was developed to investigate the purification efficiency of petroleum-containing wastewater. High-throughput sequencing was employed to investigate bacterial richness and diversity, bacterial community structure variation between spring and summer, and the effect of bacteria on petroleum-containing wastewater purification in the system. The results showed that the constructed wetland systems with A. calamus purified the petroleum-containing wastewater well. The average removal rates of petroleum pollutants, chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) were 97%, 80%, 67%, and 54%, respectively. A total of 22 strains were identified by 16SrDNA clone library gene sequencing. The bacteria mainly contained Acinetobacter, Rhizobium, and Rhodobacter . These bacteria had significant effects on organic matter decomposition and nitrogen removal, and played a major role in the removal of petroleum pollutants, COD, and TN in the constructed wetland. The bacterial richness and community diversity were higher in the summer sample than that in the spring sample. The treatment effect on petroleum pollutants was better in summer. Petroleum pollutant removal rate by the A. calamus system has a significant positive correlation with the Chao1 and Ace diversity indices (p < 0.05).